Association between triglyceride-glucose index and endometriosis: results from a cross-sectional study and Mendelian randomization study - Xu, Ting; Zhuang, Yuan; Cao, Huabin; Yang, Jingqi (Frontiers in Endocrinology, 2025)
BackgroundTriglyceride-glucose (TyG) index has been found to be associated with female reproductive disorders, but its relationship with the risk of endometriosis is unknown. Therefore, the aim of this study was to investigate this relationship.MethodsWe performed a two-sample mendelian randomization(MR) analysis to examine the causal effect of TyG index on endometriosis, and inverse variance weighting(IVW) was the main method of analysis. Then, we selected 1484 participants with endometriosis from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2006. Weighted multivariable-adjusted logistic regression and smoothed curve analysis were used to evaluate the correlation between the TyG index and endometriosis.ResultsThe results of MR analysis confirmed that higher TyG index was causally associated with the risk of endometriosis (OR=1.27, 95%CI: 1.05-1.54, P=0.01). In the cross-sectional study, subjects in the highest quartile of TyG index had the highest risk of incident endometriosis after adjusting for covariates(OR = 2.41, 95% CI:1.31-4.44, P for trend <0.01). The smoothed curve analysis also revealed a positive linear correlation between TyG index and endometriosis.ConclusionOur study confirms that a higher TyG index is associated with an increased risk of endometriosis by MR analysis and cross-sectional study. These findings suggested that TyG index could serve as a biomarker in identifying individuals who may be at a higher risk for developing endometriosis. Further research is needed to explore the potential clinical implications of these findings and to elucidate the underlying mechanisms behind this observed relationship.